RESEPSI ATAS PERUPA JERMAN PADA HARIAN KOMPAS DAN MAJALAH TEMPO EDISI 2000 – 2007 - Dian Swandayani; Nurhadi Nurhadi; Iman Santoso (Jurnal Penelitian Humaniora, 2011)
Indonesian culture gets a big influence of foreign culture. The acculturation of the culture has been going on until today. Media becomes a vehicle for spreading the foreign culture in the modern era. In the media certain values are contested to gain major influence. One of the cultural aspects getting the foreign cultural influence is fine arts. In this field, Germany is one of the developed  countries that develop fine arts and promote (penetrate) culture, particularly fine arts, to other countries in the world, including Indonesia. Regarding the fact, this article tries to explain the Indonesian society’s reception of German fine artists and their works as reflected in articles published in Kompas daily and Tempo magazine in 2000-2007 edition. Reception theory and content analysis were used in this study that tried to find the pattern and form of acculturation of German culture in Indonesia today